Caracterização experimental e teórica do ponto de orvalho da mistura metano - etanol - Lino, Luiz Henrique Meneghel (2021)
The use of gas-lift system for chemical injection is a smart solution in many cases where, operating wells have the system already installed. However, the gas-lift lines were projected to operate with single phase gaseous flow. Consequently, the presence of liquids inside the lines may damage the valves, causing reliability issues to system. Therefore, the phase envelop of the mixture natural gas – inhibitor must be known to ensure the operation at the gaseous phase region of the diagram. Since methane is the main gas in the natural gas, and ethanol is one of the most popular gas hydrates inhibitor, the goal of this work is to experimentally determinate the dew point curve of the system methane – ethanol in pressures up to 9 MPa, temperatures ranging from 313.15 K to 353.15 K in the hydrocarbon rich are of the diagram (molar fraction of methane above 93%). For this purpose, the isothermal synthetic method is applied with phase transition, which is detected with three techniques: visual, graphical and acoustic. The experimental results were modeled with Cubic-Plus-Association (CPA) equation of state. The 2B and 3B association schemes coupled with the CPA and the best temperature dependency of the binary interaction parameter (BIP) were tested. The ultrasonic technique and the visual technique showed results in agreement with the results in the literature. For the thermodynamic model, the 2B association scheme shower a batter predictive performance and the BIP used was temperature independent.